Original jade ice pattern marble tile and preparation method thereof

By setting up a multi-layer structure on the tiles and mixing raw materials for fuse and protective glaze, the problem of insufficient stability of the glaze layer of existing microcrystalline marble tiles is solved, and the production of high-quality large-size tiles is achieved, with excellent thermal stability and durability.

CN119684038AActive Publication Date: 2025-03-25FOSHAN JINZHULIN NEW MATERIAL TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411800251.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The internal bonding force of the existing microcrystalline marble tiles is poor, resulting in the overall stability of the glaze layer not being up to standard, affecting the environmental suitability and durability of the tiles.

Method used

A technical solution for original jade ice pattern marble ceramic tiles is adopted. By setting up a blank, a base glaze layer, an ink layer, a fuse layer and a protective glaze layer, and specifically mixing the fuse and the raw materials of the protective glaze, the expansion coefficients of the fuse layer and the protective glaze layer are matched, thereby improving the thermal stability and durability of the glaze layer.

Benefits of technology

The surface texture of the ceramic tile is close to that of natural marble, the thermal stability and durability of the glaze layer are significantly improved, can resist the influence of changes in the external environment, and have high hardness and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684038A_ABST
    Figure CN119684038A_ABST
Patent Text Reader

Abstract

The invention discloses an original jade ice pattern marble tile and a preparation method thereof, and belongs to the field of ceramics. The original jade ice pattern marble tile comprises a green body, a ground glaze layer, an ink layer, a frit layer and a protective glaze layer which are arranged in sequence, frits comprise a first frit, and the first frit is prepared from the following raw materials in percentage by weight: 50-55% of silicon dioxide; 16 to 19 percent of aluminum oxide; 2-3.8% of sodium oxide; 4-6.2% of potassium oxide; 1.2 to 2.6 percent of magnesium oxide; 4-6% of calcium carbonate; 4.9 to 6.8 percent of strontium carbonate; 7.5 to 9.5 percent of zinc oxide; the protective glaze comprises the following raw materials in percentage by weight: 60-64% of silicon dioxide; 2.5%-4.5% of sodium oxide; 1.5-3% of potassium oxide; 3-5% of magnesium oxide; 7-9% of aluminum oxide; 11 to 13.5 percent of barium carbonate; 1-3% of calcium carbonate; and 5-7% of zinc oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of ceramics, and in particular to a raw jade ice-textured marble tile and a preparation method thereof. Background Art

[0002] Glaze is an indispensable part of the ceramic production process. Glaze gives ceramics color, texture and gloss. The application classification of ceramics mainly includes containers, art exhibits and tiles. For tiles, glaze not only gives the tile glaze color, texture and gloss, but also determines the hardness and stability of the tile glaze layer.

[0003] Marble tiles are a popular type of tile, often used for background wall decoration. With the improvement of living standards, the previous imitation of marble texture effects only through screen printing and inkjet can no longer meet higher demands. Some people add microcrystalline frits to the glaze to make the glaze layer of the tile closer to the texture and gloss of marble.

[0004] However, the existing microcrystalline marble tiles have poor internal bonding strength of the glaze layer, resulting in the problem of poor overall stability of the glaze layer, which affects the environmental applicability and durability of the tiles. Summary of the invention

[0005] In order to obtain a glaze layer with a good marble effect and improve the thermal stability of the glaze layer, the present application provides a jade ice-patterned marble tile and a preparation method thereof.

[0006] In the first aspect, the present application provides a jade ice marble tile adopting the following technical solution: A jade ice marble tile, comprising a green body, a base glaze layer, an ink layer, a frit layer and a protective glaze layer arranged in sequence, wherein the base glaze layer is prepared by base glaze, the frit layer is prepared by frit, and the protective glaze layer is prepared by protective glaze; The frit includes a first frit, which is prepared by raw materials including the following weight percentages: 50-55% silicon dioxide; 16-19% aluminum oxide; 2-3.8% sodium oxide; 4-6.2% potassium oxide; 1.2-2.6% magnesium oxide; 4-6% calcium carbonate; 4.9-6.8% strontium carbonate; and 7.5-9.5% zinc oxide. The protective glaze comprises the following raw materials in weight percentage: 60-64% silicon dioxide; 2.5-4.5% sodium oxide; 1.5-3% potassium oxide; 3-5% magnesium oxide; 7-9% aluminum oxide; 11-13.5% barium carbonate; 1-3% calcium carbonate; and 5-7% zinc oxide.

[0007] By adopting the above technical scheme, the raw material composition of the protective glaze makes the texture of the tile surface close to the effect of the natural marble pickling surface, and the crystallization effect of the protective glaze layer is delicate and soft, thus presenting a natural patina, and combined with the frit layer, the color of the tile surface is balanced, the surface gloss is warmer and thicker, and the color is close to the original jade.

[0008] In the past, ceramics with texture effects similar to the above could only be achieved on small-sized art ceramic exhibits. If the glaze layer area is increased, the stability of the glaze layer will deteriorate, so it is difficult to apply to large-sized ceramic tile products. However, through the combination of the first frit composed of the above raw materials and the protective glaze, while presenting an ideal texture, the expansion coefficients of the frit layer and the protective glaze layer are matched, reducing the stress concentration of the overall glaze layer after firing, so as to ensure that the part of the overall glaze layer close to the outside world has sufficient thermal stability to resist the impact of changes in the external environment, thereby improving the stability and durability of the glaze layer.

[0009] In addition, while ensuring the matching of expansion coefficients, the first frit has a high aluminum oxide content, so the tile surface has higher hardness and wear resistance. The raw material composition of the protective glaze ensures that the raw materials can be melted while reducing the amount of calcium carbonate, thereby improving the tile surface's resistance to acid and alkali corrosion.

[0010] Optionally, the frit includes a first frit and a second frit configured in a weight ratio of (1.5-4):1; The second frit is prepared by raw materials comprising the following weight percentages: Silicon dioxide 56-60%; aluminum oxide 6.5-8%; sodium oxide 0.3-0.8%; potassium oxide 7-8.5%; calcium carbonate 12-13%; barium carbonate 2.5-3.8%; zinc oxide 10-12%.

[0011] By adopting the above technical solution, the first frit and the second frit together form a frit layer, which improves the expansion coefficient matching between the frit layer and the protective glaze layer, and at the same time improves the density of the frit layer structural skeleton, thereby further improving the surface hardness and wear resistance of the tile.

[0012] Optionally, the base glaze is prepared from the following raw materials in the following weight percentages: Silicon dioxide 78-85%; sodium oxide 0.3-2%; potassium oxide 10-14%; aluminum oxide 2-5%; calcium carbonate 1-3.5%.

[0013] By adopting the above technical solution, since the composition of the frit layer and the composition of the protective glaze layer are properly matched, the range of base glaze options is wider and the bonding stability between the body and the glaze layer can be ensured.

[0014] Optionally, the frit has a fineness of 60 to 120 meshes.

[0015] By adopting the above technical solution, the above fineness of the frit helps to form a stable frit layer and better combine with the protective glaze layer.

[0016] In the second aspect, the present application provides a method for preparing a raw jade ice marble tile using the following technical solution: A method for preparing a raw jade ice marble tile, comprising the following steps: The protective glaze is added with water to prepare a protective glaze slurry; Add water to the base glaze to make base glaze slurry; Applying base glaze slurry on the surface of the green body to form a base glaze layer; forming an ink layer on the surface of the base glaze layer; Distributing frit on the surface of the base glaze layer to form a frit layer; applying a cellulose aqueous solution to the surface of the frit layer to form irregular cracks; Applying protective glaze slurry on the surface of the frit layer to form a protective glaze layer; It is fired at high temperature and the surface is soft-polished after firing to make marble tiles.

[0017] By adopting the above technical scheme, the base glaze layer, ink layer, frit layer and protective glaze layer are formed step by step, wherein a cellulose aqueous solution is applied to shrink the surface of the frit layer to form irregular cracks, and then the protective glaze layer is covered to protect the cracks, thereby visually simulating the ice texture of the patina and tactilely ensuring the smooth touch of the tile surface.

[0018] Optionally, the high temperature sintering temperature is 1120-1200° C., and the high temperature sintering time is 40-60 min.

[0019] By adopting the above technical scheme, since the composition of the frit layer and the protective glaze layer are properly matched, the temperature range of high-temperature firing is relaxed, the bonding stability between the frit layer and the protective glaze layer can be ensured, and the overall glaze layer can have higher hardness and wear resistance.

[0020] Optionally, the specific gravity of the protective glaze slurry is 1.2 to 1.5 g / cm 3 The glaze amount of the protective glaze slurry is 250-400 g / m 2 The specific gravity of the base glaze slurry is 1.7 to 2.1 g / cm 3 The glaze amount of the base glaze slurry is 580-750g / m 2 .

[0021] Optionally, the amount of the frit is 1800-2300 g / m 2 .

[0022] By adopting the above technical solution, the above glazing amount and material distribution amount are helpful to improve the overall stability of the glaze layer.

[0023] Optionally, the method for preparing the frit comprises the following steps: The raw materials of the frit are mixed, melted at 1500-1550° C., the molten system is uniformly cooled, and crushed to a fineness of 60-120 meshes to obtain a frit.

[0024] Optionally, the cellulose aqueous solution is prepared by mixing sodium carboxymethyl cellulose and water, and the specific gravity of the cellulose aqueous solution is 0.8-1.3 g / cm 3 The amount of cellulose aqueous solution applied is 70 to 95 g / m 2 .

[0025] By adopting the above technical solution, the above cellulose aqueous solution can form irregular cracks on the surface of the frit layer and maintain the stability of the frit layer.

[0026] Optionally, the brightness of the semi-finished product after firing is 45 to 50 degrees, and the brightness of the finished product after surface soft polishing is 47 to 53 degrees.

[0027] Optionally, the protective glaze and the base glaze both have a 325-mesh sieve residue of 0.3%.

[0028] In summary, this application has the following beneficial effects: 1. The raw material composition of the protective glaze of the present application makes the surface texture of the tile close to the effect of the acid-washed surface of natural marble, and the crystallization effect of the protective glaze layer is delicate and soft, thus presenting a natural patina feeling, and the frit layer makes the surface color of the tile balanced, the surface brightness is more warm and thick, and the color is close to the original jade. And through the combination of the first frit composed of the above raw materials and the protective glaze, while presenting an ideal texture, the expansion coefficients of the frit layer and the protective glaze layer are matched, reducing the stress concentration of the overall glaze layer after firing, so as to ensure that the part of the overall glaze layer close to the outside world has sufficient thermal stability, thereby improving the stability and durability of the glaze layer.

[0029] 2. The present application may also choose to form a frit layer with the first frit and the second frit together, thereby improving the expansion coefficient matching between the frit layer and the protective glaze layer, and at the same time improving the density of the frit layer structural skeleton, thereby further improving the surface hardness and wear resistance of the tile. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a photo of the original jade ice-patterned marble tile of Example 1 of the present application. DETAILED DESCRIPTION

[0031] The following is combined with Figure 1 This application is described in further detail.

[0032] The general microcrystalline marble tile glaze layer will mix the frit with the surface glaze and apply it to the surface of the ink layer for firing to increase the hardness and wear resistance of the glaze layer. However, this cannot achieve the requirements of visually having an ice texture and jade transparency, and being smooth to the touch without feeling cracks.

[0033] Therefore, the present application successively forms a frit layer and a protective glaze layer on the ceramic tile to balance the visual and tactile requirements. In order to overcome the thermal stability problem caused by the stratification of the frit and the protective glaze, the present application specifically formulates the raw material composition of the frit and the protective glaze so that the expansion coefficients of the frit layer and the protective glaze layer match, thereby ensuring the overall stability of the glaze layer.

[0034] Preparation Example 1 The method for preparing the first frit comprises the following steps: The raw materials of the first sintered block are weighed in proportion. The raw material composition of the first sintered block is 50% silicon dioxide, 19% aluminum oxide, 2.8% sodium oxide, 6.2% potassium oxide, 2% magnesium oxide, 6% calcium carbonate, 5.6% strontium carbonate and 8.4% zinc oxide.

[0035] The raw materials of the first frit are mixed, melted at 1550°C, the molten system is uniformly cooled, crushed and the portion between 60 and 120 mesh sieves is taken to obtain the first frit.

[0036] Preparation Example 2 The method for preparing the first frit comprises the following steps: The raw materials of the first sintered block are weighed in proportion. The raw material composition of the first sintered block is 55% silicon dioxide, 16% aluminum oxide, 3.8% sodium oxide, 4% potassium oxide, 1.2% magnesium oxide, 5.6% calcium carbonate, 4.9% strontium carbonate and 9.5% zinc oxide.

[0037] The raw materials of the first frit are mixed, melted at 1550°C, the molten system is uniformly cooled, crushed and the portion between 60 and 120 mesh sieves is taken to obtain the first frit.

[0038] Preparation Example 3 The method for preparing the first frit comprises the following steps: The raw materials of the first sintered block are weighed in proportion. The raw material composition of the first sintered block is 54% silicon dioxide, 18% aluminum oxide, 2% sodium oxide, 5.1% potassium oxide, 2.6% magnesium oxide, 4% calcium carbonate, 6.8% strontium carbonate and 7.5% zinc oxide.

[0039] The raw materials of the first frit are mixed, melted at 1550°C, the molten system is uniformly cooled, crushed and the portion between 60 and 120 mesh sieves is taken to obtain the first frit.

[0040] Preparation Example 4 The method for preparing the second frit comprises the following steps: The raw materials of the second frit are weighed in proportion. The raw material composition of the second frit is 60% silicon dioxide, 6.5% aluminum oxide, 0.3% sodium oxide, 8.5% potassium oxide, 12.2% calcium carbonate, 2.5% barium carbonate and 10% zinc oxide.

[0041] The raw materials of the second frit are mixed, melted at 1500°C, cooled after the molten system is uniform, crushed and the portion between 60 and 120 mesh sieves is taken to obtain the second frit.

[0042] Preparation Example 5 The method for preparing the second frit comprises the following steps: The raw materials of the second frit are weighed in proportion. The raw material composition of the second frit is 56% silicon dioxide, 8% aluminum oxide, 0.8% sodium oxide, 7% potassium oxide, 13% calcium carbonate, 3.2% barium carbonate and 12% zinc oxide.

[0043] The raw materials of the second frit are mixed, melted at 1500°C, cooled after the molten system is uniform, crushed and the portion between 60 and 120 mesh sieves is taken to obtain the second frit.

[0044] Preparation Example 6 The method for preparing the second frit comprises the following steps: The raw materials of the second frit are weighed in proportion. The raw material composition of the second frit is 57% silicon dioxide, 7.3% aluminum oxide, 0.6% sodium oxide, 7.8% potassium oxide, 12% calcium carbonate, 3.8% barium carbonate, and 11.5% zinc oxide.

[0045] The raw materials of the second frit are mixed, melted at 1500°C, cooled after the molten system is uniform, crushed and the portion between 60 and 120 mesh sieves is taken to obtain the second frit.

[0046] Comparative Preparation Example 1 The method for preparing the first frit comprises the following steps: The raw materials of the first frit are weighed in proportion. The raw material composition of the first frit is 47.5% silicon dioxide, 19% aluminum oxide, 0.3% sodium oxide, 8.5% potassium oxide, 12.2% calcium carbonate, 2.5% barium carbonate and 10% zinc oxide.

[0047] The raw materials of the first frit are mixed, melted at 1500° C., the molten system is uniformly cooled, crushed and the portion between 60 and 120 mesh sieves is taken to obtain the first frit.

[0048] Comparative Preparation Example 2 The method for preparing the first frit comprises the following steps: The raw materials of the first sintered block are weighed in proportion. The raw material composition of the first sintered block is 50% silicon dioxide, 19% aluminum oxide, 2.8% sodium oxide, 6.2% potassium oxide, 2% magnesium oxide, 6% calcium carbonate, 3.9% strontium carbonate, 1.7% barium carbonate and 8.4% zinc oxide.

[0049] The raw materials of the first frit are mixed, melted at 1550°C, the molten system is uniformly cooled, crushed and the portion between 60 and 120 mesh sieves is taken to obtain the first frit.

[0050] Example 1 A method for preparing raw jade ice-textured marble tiles comprises the following steps: S1. Weigh the raw materials of protective glaze according to the proportion. The raw materials of protective glaze are composed of 60% silicon dioxide, 4% sodium oxide, 1.5% potassium oxide, 4.5% magnesium oxide, 9% aluminum oxide, 12.5% ​​barium carbonate, 3% calcium carbonate, and 5.5% zinc oxide. Add water to make protective glaze slurry, grind to a fineness of 0.3% on a 325 mesh sieve, and the specific gravity of the protective glaze slurry is 1.5g / cm 3 .

[0051] S2. Weigh the raw materials of the base glaze according to the proportion. The raw materials of the base glaze are composed of 78% silicon dioxide, 0.9% sodium oxide, 12.6% potassium oxide, 5% aluminum oxide, and 3.5% calcium carbonate. Add water to the base glaze to make a base glaze slurry, grind it to a fineness of 0.3% on a 325 mesh sieve, and the specific gravity of the base glaze slurry is 2.1g / cm 3 .

[0052] S3. Apply base glaze slurry on the surface of the blank. The amount of base glaze slurry applied is 580g / m 2 , forming a bottom glaze layer.

[0053] S4. Spray ink on the surface of the base glaze layer, select corresponding ink according to the required color, and form an ink layer.

[0054] S5. The frit is applied on the surface of the bottom glaze layer. The frit is specifically the first frit prepared in Preparation Example 1. The amount of the first frit is 1800 g / m 2 , forming a frit layer.

[0055] S6. Apply a cellulose aqueous solution to the surface of the frit layer. The cellulose aqueous solution is prepared by mixing sodium carboxymethyl cellulose and water. The specific gravity of the cellulose aqueous solution is 1.3 g / cm 3 The amount of cellulose aqueous solution applied is 70 g / m 2 After applying the cellulose aqueous solution, the frit layer shrinks and forms irregular cracks.

[0056] S7. Apply protective glaze slurry on the surface of the frit layer. The amount of protective glaze slurry applied is 250g / m 2 ; Form a protective glaze layer.

[0057] S8. Firing at 1120℃ for 80min, the brightness of the semi-finished product after firing is 45 degrees, and the surface is soft-polished with an abrasive brush and a fiber module, and the brightness of the finished product is 47 degrees, making marble tiles.

[0058] Example 2 A method for preparing raw jade ice-textured marble tiles comprises the following steps: S1. Weigh the raw materials of protective glaze according to the proportion. The raw materials of protective glaze are composed of 64% silicon dioxide, 2.5% sodium oxide, 2% potassium oxide, 3% magnesium oxide, 7% aluminum oxide, 13.5% barium carbonate, 1% calcium carbonate, and 7% zinc oxide. Add water to make protective glaze slurry, grind to a fineness of 0.3% on a 325 mesh sieve, and the specific gravity of the protective glaze slurry is 1.2g / cm 3 .

[0059] S2. Weigh the raw materials of the base glaze according to the proportion. The raw materials of the base glaze are 85% silicon dioxide, 3% sodium oxide, 10% potassium oxide, 3% aluminum oxide, and 1% calcium carbonate. Add water to the base glaze to make a base glaze slurry, grind it to a fineness of 0.3% on a 325 mesh sieve, and the specific gravity of the base glaze slurry is 1.7g / cm 3 .

[0060] S3. Apply base glaze slurry on the surface of the blank. The amount of base glaze slurry applied is 750g / m 2 , forming a bottom glaze layer.

[0061] S4. Spray ink on the surface of the base glaze layer, select corresponding ink according to the required color, and form an ink layer.

[0062] S5. The frit is applied on the surface of the bottom glaze layer. The frit is specifically the first frit prepared in Preparation Example 2. The amount of the first frit is 2300 g / m 2 , forming a frit layer.

[0063] S6. Apply a cellulose aqueous solution to the surface of the frit layer. The cellulose aqueous solution is prepared by sodium carboxymethyl cellulose and water. The specific gravity of the cellulose aqueous solution is 0.8 g / cm 3 The amount of cellulose aqueous solution applied is 95 g / m 2 After applying the cellulose aqueous solution, the frit layer shrinks and forms irregular cracks.

[0064] S7. Apply protective glaze slurry on the surface of the frit layer, and the amount of protective glaze slurry applied is 400g / m 2 ; Form a protective glaze layer.

[0065] S8. Firing at 1200°C for 60 minutes, the brightness of the semi-finished product after firing is 50 degrees, and the surface is soft-polished with an abrasive brush and a fiber module, and the brightness of the finished product is 53 degrees, making marble tiles.

[0066] Example 3 A method for preparing raw jade ice-textured marble tiles comprises the following steps: S1. Weigh the raw materials of protective glaze according to the proportion. The raw materials of protective glaze are composed of 62% silicon dioxide, 4.5% sodium oxide, 3% potassium oxide, 5% magnesium oxide, 7.5% aluminum oxide, 11% barium carbonate, 2% calcium carbonate, and 5% zinc oxide. Add water to make protective glaze slurry, grind to a fineness of 0.3% on a 325 mesh sieve, and the specific gravity of the protective glaze slurry is 1.5g / cm 3 .

[0067] S2. Weigh the raw materials of the base glaze according to the proportion. The raw materials of the base glaze are composed of 80% silicon dioxide, 0.3% sodium oxide, 14% potassium oxide, 3% aluminum oxide, and 2.7% calcium carbonate. Add water to the base glaze to make a base glaze slurry, grind it to a fineness of 0.3% on a 325 mesh sieve, and the specific gravity of the base glaze slurry is 2.1g / cm 3 .

[0068] S3. Apply base glaze slurry on the surface of the blank. The amount of base glaze slurry applied is 580g / m 2 , forming a bottom glaze layer.

[0069] S4. Spray ink on the surface of the base glaze layer, select corresponding ink according to the required color, and form an ink layer.

[0070] S5. The frit is applied on the surface of the bottom glaze layer. The frit is specifically the first frit prepared in Preparation Example 3. The amount of the first frit is 1800 g / m 2 , forming a frit layer.

[0071] S6. Apply a cellulose aqueous solution to the surface of the frit layer. The cellulose aqueous solution is prepared by mixing sodium carboxymethyl cellulose and water. The specific gravity of the cellulose aqueous solution is 1.3 g / cm 3 The amount of cellulose aqueous solution applied is 70 g / m 2 After applying the cellulose aqueous solution, the frit layer shrinks and forms irregular cracks.

[0072] S7. Apply protective glaze slurry on the surface of the frit layer. The amount of protective glaze slurry applied is 250g / m 2 ; Form a protective glaze layer.

[0073] S8. Firing at 1120℃ for 80min, the brightness of the semi-finished product after firing is 45 degrees, and the surface is soft-polished with an abrasive brush and a fiber module, and the brightness of the finished product is 47 degrees, making marble tiles.

[0074] Example 4 A method for preparing raw jade ice marble tiles. The difference between this embodiment and embodiment 1 is that in step S5, the frit is specifically prepared by the first frit prepared in preparation example 1 and the second frit prepared in preparation example 4 in a weight ratio of 1.5:1, and the overall amount of the frit is 1800g / m 2 .

[0075] Example 5 A method for preparing raw jade ice marble tiles. The difference between this embodiment and embodiment 1 is that in step S5, the frit is specifically prepared by the first frit prepared in preparation example 1 and the second frit prepared in preparation example 5 in a weight ratio of 4:1, and the overall amount of the frit is 1800g / m 2 .

[0076] Example 6 A method for preparing raw jade ice marble tiles. The difference between this embodiment and embodiment 1 is that in step S5, the frit is specifically prepared by the first frit prepared in preparation example 1 and the second frit prepared in preparation example 6 in a weight ratio of 1.5:1, and the overall amount of the frit is 1800g / m 2 .

[0077] Comparative Example 1 A method for preparing raw jade ice-textured marble tiles. The difference between this comparative example and Example 1 is that the frit specifically adopts the first frit prepared in Comparative Preparation Example 1.

[0078] Comparative Example 2 A method for preparing raw jade ice-textured marble tiles. The difference between this comparative example and Example 1 is that the frit specifically adopts the first frit prepared in Comparative Preparation Example 2.

[0079] Comparative Example 3 A method for preparing raw jade ice-pattern marble tiles. The difference between this comparative example and Example 1 is that the frit specifically adopts the second frit prepared in Preparation Example 4.

[0080] Comparative Example 4 A method for preparing raw jade ice-patterned marble tiles. The difference between this comparative example and Example 1 is that the raw material composition of the protective glaze is 60% silicon dioxide, 4% sodium oxide, 1.5% potassium oxide, 7.5% magnesium oxide, 9% aluminum oxide, 9.5% barium carbonate, 3% calcium carbonate, and 5.5% zinc oxide.

[0081] Product performance testing The original jade ice-grain marble tiles prepared in Examples 1-6 and Comparative Examples 1-4 were used as test samples and the following tests were performed.

[0082] Evaluation of glaze performance: Sales and R&D personnel in the ceramic field were assembled into an evaluation team to conduct a comprehensive evaluation of the glaze texture, gloss, color and touch. The evaluation results are shown in Table 1.

[0083] Table 1 Thermal stability test: The marble tile sample was placed in an oven at 180°C for 1 hour, then the marble tile sample was taken out and immediately placed in water at 25°C for cooling. The above heating and cooling steps were repeated three times, and finally the surface of the glaze layer was observed for any tangible cracks. The test results are shown in Table 2.

[0084] Hardness test: Referring to JCT 908-2013 "Artificial Stone", the surface Mohs hardness of the marble tile sample was tested. The test results are shown in Table 2.

[0085] Wear resistance test: refer to GB / T 3810.7-2016 "Test methods for ceramic tiles Part 7: Determination of surface wear resistance of glazed tiles", and the test results are shown in Table 2. The higher the number of grinding revolutions required to achieve visible wear, the better the wear resistance.

[0086] Table 2 As shown in Table 1, the marble tiles obtained in Examples 1-6 all have excellent texture, gloss, color and touch, achieving the effect characteristics of original jade ice pattern. In addition, according to the feedback from senior industry personnel, Example 1 is the closest to the texture of natural marble acid-washed surface, which can be referred to Figure 1 , and the hair color of Example 6 has the heaviest feeling.

[0087] As shown in Table 2, the marble tiles obtained in Examples 1-3 exhibit good thermal stability, high hardness and high wear resistance, proving that the marble tiles have good durability. Compared with Comparative Examples 1-4, the marble tiles of Example 1 have the best comprehensive performance in terms of durability, especially being able to pass three consecutive thermal stability tests, thus proving that the raw material composition of the specific blended frit and the protective glaze is coordinated to ensure a stable combination of the frit layer and the protective glaze layer, thereby balancing the appearance performance and the actual application quality of the glaze layer.

[0088] Compared with Example 1, the wear resistance of Examples 4-6 is further improved, which proves that the first frit and the second frit jointly improve the density of the frit layer structure skeleton, thereby improving the wear resistance.

[0089] In addition, the marble tile test samples of Examples 1-6 also have good acid and alkali tolerance, and can be placed in a sodium carbonate solution with a pH of 9 and a citric acid solution with a pH of 3 for up to 168 hours respectively without any change on the surface of the glaze layer, further proving that they have good durability.

[0090] The size of the marble tiles produced in Examples 1-6 can reach 1800×900 mm, and the glaze layer of the tiles exhibits good durability, thereby achieving large-scale mass production of tiles with original jade ice pattern effects.

[0091] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A jade ice marble tile, characterized by: The invention comprises a body, a base glaze layer, an ink layer, a frit layer and a protective glaze layer which are arranged in sequence, wherein the base glaze layer is prepared by the base glaze, the frit layer is prepared by the frit, and the protective glaze layer is prepared by the protective glaze; The frit includes a first frit, which is prepared by raw materials including the following weight percentages: 50-55% silicon dioxide; 16-19% aluminum oxide; 2-3.8% sodium oxide; 4-6.2% potassium oxide; 1.2-2.6% magnesium oxide; 4-6% calcium carbonate; 4.9-6.8% strontium carbonate; and 7.5-9.5% zinc oxide. The protective glaze comprises the following raw materials in weight percentage: 60-64% silicon dioxide; 2.5-4.5% sodium oxide; 1.5-3% potassium oxide; 3-5% magnesium oxide; 7-9% aluminum oxide; 11-13.5% barium carbonate; 1-3% calcium carbonate; and 5-7% zinc oxide.

2. The original jade ice-grain marble tile according to claim 1, characterized in that: The frit includes a first frit and a second frit arranged in a weight ratio of (1.5-4):1; The second frit is prepared by raw materials comprising the following weight percentages: Silicon dioxide 56~60%; aluminum oxide 6.5~8%; sodium oxide 0.3~0.8%; potassium oxide 7~8.5%; calcium carbonate 12~13%; barium carbonate 2.5~3.8%; zinc oxide 10~12%.

3. The original jade ice-grain marble tile according to claim 1, characterized in that: The base glaze is prepared from the following raw materials in percentage by weight: Silicon dioxide 78~85%; sodium oxide 0.3~2%; potassium oxide 10~14%; aluminum oxide 2~5%; calcium carbonate 1~3.5%.

4. The original jade ice-grain marble tile according to claim 1, characterized in that: The fineness of the frit is 60-120 meshes.

5. A method for preparing a raw jade ice-grain marble tile according to any one of claims 1 to 4, characterized in that: The following steps are involved: The protective glaze is added with water to prepare a protective glaze slurry; Add water to the base glaze to make base glaze slurry; Applying base glaze slurry on the surface of the green body to form a base glaze layer; forming an ink layer on the surface of the base glaze layer; Distributing frit on the surface of the base glaze layer to form a frit layer; applying a cellulose aqueous solution to the surface of the frit layer to form irregular cracks; Applying protective glaze slurry on the surface of the frit layer to form a protective glaze layer; It is fired at high temperature and the surface is soft-polished after firing to make marble tiles.

6. The method for preparing the original jade ice-grain marble tile according to claim 5, characterized in that: The high temperature firing temperature is 1120~1200℃, and the high temperature firing time is 60~80min.

7. The method for preparing the original jade ice-grain marble tile according to claim 5, characterized in that: The specific gravity of the protective glaze slurry is 1.2-1.5 g / cm 3 The glaze amount of the protective glaze slurry is 250~400g / m 2 The specific gravity of the base glaze slurry is 1.7~2.1g / cm 3 The glaze amount of the base glaze slurry is 580~750g / m 2 .

8. The method for preparing the original jade ice-grain marble tile according to claim 5, characterized in that: The amount of the frit is 1800-2300 g / m 2 .

9. The method for preparing the original jade ice-textured marble tile according to claim 5, characterized in that: The method for preparing the frit comprises the following steps: The raw materials of the frit are mixed, melted at 1500-1550°C, the molten system is uniformly cooled, and crushed to a fineness of 60-120 meshes to obtain a frit.

10. The method for preparing the original jade ice-textured marble tile according to claim 5, characterized in that: The cellulose aqueous solution is prepared by sodium carboxymethyl cellulose and water, and the specific gravity of the cellulose aqueous solution is 0.8-1.3 g / cm 3 The amount of cellulose aqueous solution applied is 70-95 g / m 2 .

Citation Information

Patent Citations

  • Translucent apatite glass ceramic

    CA2239865A1

  • Leadless molten block enamel for bone porcelain

    CN100999415A

  • Green brick structure of single fired glass ceramic composite board

    CN104291878A

  • Composite whitening environment-friendly glaze, ceramic tile and preparation method thereof

    CN113185125A

  • One-glaze two-sided ceramic rock plate, one-glaze two-sided transparent glaze and preparation method thereof

    CN114644530A